Emergency management of dental injury; preparedness among school teachers in Bhubaneswar, India - Ramesh Nagarajappa; Debasruti Naik (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. School is the place, identified with a noticeable risk of Traumatic Dental Injuries (TDI) in children which have functional, esthetic and psychological effects. Objectives. To assess the preparedness of concerning traumatic dental injuries and their management among school teachers and also to empower the clinician to frame a set of instructions for school teachers to handle the emergencies effectively at the site of the incident. Material and Methods. A cross-sectional study was conducted among 330 school teachers enrolled in government and private schools of 24 randomly selected schools in Bhubaneswar city. A self-administered questionnaire was distributed to collect information on participants demographic characteristics, knowledge, attitude and practice about emergency management of Traumatic Dental Injury. Chi-square test with level of significance set at 5% was used for statistical analysis. Results. Statistically significant (p<0.05) correct responses were provided by 66.7% males and 35.6% females and 100% younger age teachers. Larger population perceived that their level of knowledge was not satisfactory as they responded for inadequate and don't know options which was significant in relation to gender and age (p<0.05) but not with respect to the type of school (p>0.05). All the respondents expressed the need for a training program. Conclusions. This study highlights the instantaneous need for tailor made dental health educational and preventive programs for school teachers in order to effectively manage the Traumatic Dental Injuries.